Memoirs of Haw Par villa. - Cheng, Yu Hui. (2012)
Through the years, the once flourishing Haw Par Villa has taken a back seat with Singapore’s rapid development. A summation of surveys and studies related to the villa concludes this attraction as part of Singapore’s rich heritage, yet there are insufficient records of the place. By collecting shared memories of the villa, this project aims to record and capture untold experiences of different generations of locals who have seen the place from its opening in 1938 till now, and to produce an engaging, illustrative journey. The compilation of 36 booklets, categorized into 4 different themes of environment, experiences, emotions and conversation, is a visual reflection of our local heritage that focuses on reigniting the joy of family bonding.